Kajian Pengendalian Laju Sedimen Dengan Bangunan Pengendali Di DAS Hulu Batang Gadis Propinsi Sumatera Utara - Kaharuddin, Kaharuddin; Bisri, Mohammad; Juwono, Pitojo Tri (Jurusan Teknik Pengairan, Fakultas Teknik, Universitas Brawijaya, 2014)
Hulu Batang Gadis Watershed is located in the district of Mandailing Natal province of North Sumatra . The rate of erosion in the watershed upstream Batang Gadis last 3 years has increased , it can be seen from the results of the analysis and calculation of the rate of erosion USLE method which in 2008 amounted to 307 285 tonnes / ha / year , in 2010 amounted to 318 482 tonnes / ha / year , Year 2012 of 385 336 tonnes / ha / year . This indicates an increase in the rate of erosion in 2008 - 2012 at 20:26% .. The rate of soil erosion hazard and criticality criteria of 1.41% Very Light , Light 10.92% , 17.76% Medium , Heavy and Very Heavy 49.59% ,20.32% . The results depend on the amount of sediment erosion in the watershed / sub-watershed .. Currently sediment issues have an impact on the downstream watershed upstream Batang Gadis ie the number of incoming sediment kesaluran irrigation and river silting . One attempt to overcome this problem is by building sediment control in the form of Check Dam . In this research study conducted as the proposed construction of sediment control 33 Check Dam . Successful achievement of development can reduce sediment control sediment 90.91% on average of all the bin capacity Chek Dam , while by means of sediment routing can reduce sediment by 97.39% with the operation of the check dam for 3 years . In addition to building pendali also recommended handling a land conservation treatment with a wide landing area function Buffer Zone 59.28% , Budi Region 4.57% Annual Plants , Cultivation Region Annuals 36.15% . The arrangement of the achievements of the region is a big impact on the land eroded soil erosion is very heavy 20.32% of basin area upstream Batang Gadis be 1.83% .Keyword: Erosion, sedimentation, controle structure, conservation